Effect of Stiffener Characteristics on the Seismic Behavior and Fracture Tendency of Steel Shear Walls (Fracture and Structural Integrity, 2020)
The steel plate shear walls (SPSW) are currently being considered as a lateral load resisting system. A numerical method was proposed to have a comprehensive comparison of seismic behaviors of the plane wall (PW) and stiffened plane wall (SPW) with different stiffener characteristics, having the same weight, by using finite element modeling (FEM). The model was validated by using previously published experimental works. The material and geometric nonlinearity were taken into consideration. In this paper, the effect of using stiffeners with different cross-section shapes and directions will be studied, and key issues, such as load-carrying capacity, stiffness, and energy dissipation capacity, were discussed in depth. It was found that the proposed SPW with horizontal L, T, and U stiffeners could effectively improve load-carrying capacity by about 4, 20, and 23%, respectively. Diagonally and horizontally, SPWs with U stiffeners have higher energy-dissipation capacity than PW by about 57, 50%, respectively. This method provides a combination of high-performance stiffeners form and material for improving the seismic behavior of SPW.
Keywords: Backbone curve; energy-dissipation capacity; hysteretic behavior; steel plate shear wall; seismic behavior